Evaluation of warfarin management in primary health care centers in Qatar: A retrospective cross-sectional analysis of the national dataset - Safaa Alshihab (21633677) (2024)
Background Warfarin management is associated with severe complications, highlighting the critical need to evaluate the quality of its administration. Objectives To evaluate the quality of warfarin management for patients managed in primary healthcare centers by measuring the percentage of Time in Therapeutic Range (TTR) and the proportion of extreme out-of-range international normalized ratio (INR) values. Methods This is a cross-sectional study. Data was extracted from a national dataset retrieved from the largest primary healthcare provider in Qatar. TTR was calculated using the traditional method. Inferential and descriptive analyses were performed as appropriate. Results Four hundred ninety-four patients met the inclusion criteria. The mean (SD) TTR was 45.3 % (17.5). This was significantly lower than the recommended cutoff value (P<0.001). Extreme out-of-range INR accounted for 24.7 % of total INR readings. Conclusions The management of patients taking warfarin in Qatar is inadequate. More effective strategies are warranted to ensure safe and effective therapy. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102427